Adolescent Forced Marriage and Community Misconduct: Rethinking Islamic Family Law - Larasati, Yuniar Galuh; Fernando, Henky; Barkah, Qodariah; Prasojo, Zaenuddin Hudi; Atika, Atika; SA, Romli; Masruroh, Ainul; Sintang, Suraya; Morin, Leanne (IAIN Manado, 2025)
The normalization of forced marriage as a response to adolescents' involvement in behaviors perceived by their communities as socially or religiously inappropriate, such as premarital interactions or relationships beyond culturally sanctioned norms, may result in complex and disproportionate consequences for the adolescents involved. This study addresses gaps in prior research by exploring the characteristics of these cases, the prevailing community interpretations, and the rationale behind legitimizing forced marriage as a form of moral resolution. The findings highlight three key insights. First, forced marriage is often constructed as a culturally informed response to situations involving behaviors considered socially sensitive. Second, People commonly understand such practices as preserving family honor and fulfilling communal or religious expectations. Third, these responses are typically driven more by shared moral and cultural frameworks than by considerations of the adolescent's rights and well-being. This study contributes to the discourse on Islamic family law by illustrating how community-based interpretations of morality, honor, and religious obligation may shape the application of legal and ethical principles in cases involving adolescents, particularly within the framework of protection and justice for minors.